2011
DOI: 10.1007/s00421-011-2134-6
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental effects of West to East transmeridian flight on jump performance

Abstract: It is perceived that long haul travel, comprising of rapid movement across several time zones is detrimental to performance in elite athletes. However, available data is equivocal on the impact of long haul travel on maximal explosive movements. The aim of this study was to quantify the impact of long haul travel on lower body muscle performance. Five elite Australian skeleton athletes (1 M, 4 F) undertook long haul flight from Australia to Canada (LH(travel)), while seven national team Canadian skeleton athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 25 publications
2
45
2
1
Order By: Relevance
“…Equally, it is possible that the Australians' effort reflected travel fatigue 34 and reduced wellness 17 stemming from playing a match on the third day after arrival in Bolivia, after 30 h of long-haul travel and a 10 h time zone change. Long-haul travel is known to reduce counter-movement jump performance, 35 which in turn is related to the amount of HiVR performed by elite team sport athletes in competition. 36 In accordance with reduced capacity 17 at high altitude, 5 6 the peak 5 min running distance on arrival at 3600 m was 13-16% lower for Bolivian and Australians, respectively, than that reported with the same method at 1600 m. 3 As the magnitude of this standardised effect was evident for both Australians and Bolivians, it is intriguing that lifelong residence at altitude did not offer a protective effect against altitude for the Bolivians.…”
Section: Discussionmentioning
confidence: 99%
“…Equally, it is possible that the Australians' effort reflected travel fatigue 34 and reduced wellness 17 stemming from playing a match on the third day after arrival in Bolivia, after 30 h of long-haul travel and a 10 h time zone change. Long-haul travel is known to reduce counter-movement jump performance, 35 which in turn is related to the amount of HiVR performed by elite team sport athletes in competition. 36 In accordance with reduced capacity 17 at high altitude, 5 6 the peak 5 min running distance on arrival at 3600 m was 13-16% lower for Bolivian and Australians, respectively, than that reported with the same method at 1600 m. 3 As the magnitude of this standardised effect was evident for both Australians and Bolivians, it is intriguing that lifelong residence at altitude did not offer a protective effect against altitude for the Bolivians.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a prospective study, Chapman et al 50 assessed post-travel jump performance in 12 national team skeleton athletes (five from Australia and seven from Canada) and reported a significant variation in performance over the testing window. After initial performance deterioration in some jumping tasks, the peak velocity, mean velocity and jump power eccentric utilisation ratios (an indicator of power performance) for the travel group all significantly increased 2 days after the long-haul flight.…”
Section: Jet Lagmentioning
confidence: 99%
“…Conversely, travel fatigue symptoms are induced by the demands of air travel, including the travel schedule (departure, stop-over and arrival times), mild hypoxia and cramped conditions. Whilst several studies have reported the detrimental effects of long-haul air travel east and west across multiple time-zones on performance, physiological and perceptual responses [6][7][8] , few studies have assessed the impact of long-haul air travel north and south with minimal time-zone changes. Due to minimal time-zone changes, it is presumed that travel fatigue symptoms are more likely to be present than jet-lag symptoms following air travel north and south between Australia and Asia.…”
Section: Introductionmentioning
confidence: 99%